COMPARATIVE ANALYSIS OF STRATEGIES FOR HEDGING A SECURITIES PORTFOLIO WITH FUTURES - V. V. Lakshina; K. A. Lapshina (Финансы: теория и практика)
Hedging is one of the most popular strategies of the market risk management. The main purpose of hedging is to reduce the volatility (or variability) of the yield on the portfolio composed of spot assets and hedging tools. The hedging tools may consist of futures contracts, options and off-exchange tools such as forwards and swaps. Hedging strategies using futures contracts are the most simple ones and therefore very common in practice. The purpose of the study is to compare four hedging strategies where a share is a spot asset and a futures contract is a hedging asset. The results of comparison showed the strategy based on the calculation of the internal rate of return to be the most effective. According to the other two criteria, the above strategy and the least squares method turned out to be the best. A correction for heteroscedasticity made with the use of the maximum likelihood method did not improve the hedging performance of shares. This work can be developed in several directions, namely: consideration of option hedging strategies; adding other spot assets, e.g. exchange commodities or currencies, to the portfolio; taking into account the degree of the investor’s risk aversion in calculating the hedge ratio; introduction of transaction costs into the model.